First record of an invasive shrimp from the family Processidae (Crustacea, Decapoda) in the Mediterranean Sea - LEVITT, Y.; GRAVE, S. D.; SHENKAR, N. (Mediterranean Marine Science, 2014)
This is the first recording on the genus Nikoides Paulson, 1875 in the Mediterranean Sea, with remarks on taxonomy and ecology.